The importance of the ligation of the inferior thyroid artery in parathyroid function after subtotal thyroidectomy - Araujo Filho, Vergilius José Furtado de; Silva Filho, Gilberto Britto e; Brandão, Lenine Garcia; Santos, Luiz Roberto Medina dos; Ferraz, Alberto R. (Revista do Hospital das Clínicas, 2000)
We prospectively studied the effects of the ligation of the inferior thyroid artery (ITA) on postoperative hypoparathyroidism in 48 patients who underwent functional subtotal thyroidectomy. Patients were randomized into two groups: A, with bilateral ligation of the ITA and B, without ligation of the ITA. Parathyroid function was checked preoperatively and after surgery by clinical examination and measurement of total calcium, intact PTH, urinary calcium, and AMPc. RESULTS: A significant incidence of postoperative hypocalcemia occurred: 17% in group A and 13% in B on the 4th postoperative day. Six months later, the incidence was 5% in Group A and 0% in Group B. These differences were not statistically significant between the two groups, and neither were any of the other clinical and laboratory observations. CONCLUSION: The ligation of the ITA was not an important causal factor for the occurrence of postoperative hypocalcemia after subtotal thyroidectomy.